Nanopore-based complete genome sequence of a Sri Lankan cassava mosaic virus (Geminivirus) strain from Thailand - Leiva Sandoval, Ana Maria; Siriwan, Wanwisa; López Alvarez, Diana; Barrantes, Israel; Hemniam, Nuannapa; Saokham, Kingkan; Cuéllar, Wilmer Jose (American Society for Microbiology, 2020)
Sri Lankan cassava mosaic virus is an emerging pathogen in Southeast Asia. Here, we report the complete genome of a Thai isolate obtained using Nanopore technology. The isolate was collected in 2019 from the northeastern province of Surin, soon after disease eradication was reported in the country.